2020
DOI: 10.1177/2309499020978308
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of magnetic resonance imaging for diagnosing unstable ligament injuries around the thumb metacarpophalangeal joint: A comparison to arthroscopy

Abstract: Purpose: This study aimed to assess the accuracy of MRI in identifying ulnar collateral ligament (UCL), radial collateral ligament (RCL), and volar plate (VP) injuries of the metacarpophalangeal joint (MCPJ) of the thumb by comparing with diagnostic arthroscopy. Methods: A total of 56 consecutive patients (56 thumbs) who underwent arthroscopy of MCPJ of thumb were enrolled. MRI findings reviewed by consensus reading of two blinded radiologists were compared with arthroscopic examination. Statistical data, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…MRI is also used to evaluate the injury and define its characteristics, including location and displacement [ 8 ]. However, according to a recent study in which MRI was used for the diagnosis of ligament injuries around the thumb MCP joint, researchers concluded that MRI is moderately effective, but is more sensitive in diagnosing acute injuries [ 2 ]. This was the finding in our case as well, as MRI was not sensitive enough to detect the volar plate rupture 2 months after the initial injury and a clinical diagnosis was made that led to surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MRI is also used to evaluate the injury and define its characteristics, including location and displacement [ 8 ]. However, according to a recent study in which MRI was used for the diagnosis of ligament injuries around the thumb MCP joint, researchers concluded that MRI is moderately effective, but is more sensitive in diagnosing acute injuries [ 2 ]. This was the finding in our case as well, as MRI was not sensitive enough to detect the volar plate rupture 2 months after the initial injury and a clinical diagnosis was made that led to surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The thumb volar plate (also referred to as volar ligament, palmar plate, or palmar ligament) is a thick ligament on the underside of the metacarpophalangeal (MCP) joint of the thumb, which reinforces the joint capsule, enhances joint stability, and limits hyperextension [ 1 , 2 ]. The volar ligament is loose when the MCP joint is in flexion and tight when the MCP joint lies in extension.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, MRI has the utility of being able to identify concurrent palmar or other ligament injuries and bony contusions (25). For thumb MCP joint ligamentous injuries, 3.0 Tesla MRI has been shown to provide improved diagnostic accuracy compared with 1.5 Tesla with findings being consistent with arthroscopy in 76.9% and 47.1% of cases, respectively (37). MRI also showed better correspondence with arthroscopy findings in acute compared with chronic injuries.…”
Section: Diagnosismentioning
confidence: 99%